Gestão dos riscos ocupacionais no manejo do lodo de estações de tratamento de esgotos e a NBR ISO 31000 - Silva, Alysson Rogerio da (Universidade Federal de São Carlos, 2019)
The wastewater treatment plants (WWTP) performance a crucial role in maintaining the health of the population by treating domestic sewage and returning treated effluent to the water sources. However, generate a considerable amount of sewage sludge and this solid waste must be destined, through recovery, reuse or recycling, or disposed as waste in landfill, when all destination possibilities are exhausted, as provided by National Policy on Solid Waste. The costs related to the management of sewage sludge can represent 60% of the operational costs of the WWTP. In addition, sewage sludge can be dangerous to human health and workers who act directly or indirectly in their management are exposed to various occupational risks. This research objects to analyses the relationship between the sewage sludge management and their occupational risks, through a risk management proposal, based on ISO 31000, which apply methods of identification, analysis, assessment and control of occupational risks in two medium-sized WWTP in the interior of São Paulo state, using different technologies, conventional activated sludge and UASB anaerobic reactors. Among the main occupational risks assessed, were considered critical the exposure to pathogenic microorganisms dispersed in the air and in direct accidental contact, and the risk of accidental drives of equipment during maintenance. It can be seen that there is still a lot of resistance both from employees and from employers about health and safety at work. Much is due to cultural and social factors, and therefore, there will always be a need to update legal instruments and intensify surveillance. In addition, it is necessary to promote, on a frequent basis, the awareness of employees and, especially, of employers, discussing the role of managers of basic sanitation services, especially in the treatment of sewage, in the process of development of work safety culture in the companies.
Occupational risks management in sewage sludge management and ISO 31000
Gestión de riesgos laborales en el manejo de lodos de aguas residuales e ISO 31000
Keywords: Manejo do LETE; Lodo de esgoto; Gestão de riscos ocupacionais; Saúde e segurança do trabalho; NBR ISO 31000; Sewage sludge management; Sewage sludge; Occupational risk management; Health and safety; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS; ENGENHARIAS::ENGENHARIA SANITARIA; ENGENHARIAS